Kako do bolj fleksibilne predstavitve poslovnih pravil? - Jaklič, Jurij (Uporabna informatika (Ljubljana), 1998)
In the paper we propose and describe a way of business rules representation within information systems that enables their greater flexibility and reusability. The representation is based on the three level view of decission rules, object oriented models and decision tables. The proposed approach of representation was carried through and tested in two ways: (i) by designing a prototype which fully implemented the three level view of decission rules, and (ii) by analyzing its possible applications within a selected case problem.
Keywords: informacijski sistemi; organizacija poslovanja; podjetništvo; pravila; uporaba računalnikov